Aging, private health expenditures and environment quality - Fatma Safi (Kiel Institute for the World Economy (IfW), 2016)
This paper presents a simple two-period overlapping generation's model with uncertain lifetimes that contains environmental and health issues. It investigates an intergenerational conflict between old and young generations as regards two defensive expenditures, offsetting the influence of a worsening environment, represented here by health care and environmental investment. Workers support environmental maintenance while retirees prefer investing in healthcare. The author shows that an increasing support for private health expenditures in an aging economy leads to a higher level of capital accumulation and leads also to a higher level of environmental quality only if the maintenance efforts are larger than consumption externalities.
Keywords: D91; J11; Q20; 330; aging; environmental expenditures; environmental quality; overlapping generations; age-based conflict